Analysis of Market Responses to Lockdown Effect of Covid-19 Pandemic in Indonesia and Malaysia (Studies on Companies Listed on Jakarta Islamic Index and FTSE Bursa Malaysia Hijrah Syariah Index) - Afny Suci Ningsih; Ely Windarti Hastuti; Salysya Dzakiyah Al Abidah (IAEI, 2023)
The announcement of lockdowns in Indonesia and Malaysia due to Covid-19 affected the formation of stock price fluctuations because stock prices continued to change, known as volatility. Measurements on the stock market that occur as a result of an event use the market response that is determined by abnormal returns and trading volume activity. The purpose of this study was to analyze abnormal returns and trading volume activity on the lockdown effect in Indonesia and Malaysia. This type of research is quantitative. The samples used were 19 companies listed on the Jakarta Islamic Index which were consistently listed during the lockdown due to Covid-19 and the 10 best constituents on the FTSE Bursa Malaysia Hijrah Syariah. The data analysis technique used is the normality test using the Kolmogorov-Smirnov test and the significance test. The results of the study showed that there was no reaction to abnormal returns when setting the Large Scale Social Restrictions policy and Imposing Restrictions on Community Activities in Indonesia, but there was a reaction to abnormal returns when setting the Movement Restriction Order policy in Malaysia. As for trading volume activity, there was no reaction to the enactment of the Large-Scale Social Restrictions policy, the Enforcement of Restrictions on Community Activities, and Orders to Restrict Movement in Indonesia and Malaysia.